PENGARUH MEDIA VIDEO DETEKSI DINI KANKER SERVIKS TERHADAP PENINGKATAN PENGETAHUAN WANITA USIA SUBUR (WUS) - Niken Purbowati; Junengsih Junengsih; Niki Rian Putri; Aticeh Aticeh (Poltekkes Kemenkes Jakarta III, 2021)
Efforts to increase the knowledge of women of childbearing age in preventing cervical cancer, one of the efforts made with health education. The lack of knowledge and awareness of women to detect cervical cancer early because it has not been exposed to information about this. Pasar Baru Village area the lowest coverage of cervical cancer early detection in Tangerang City, by 17% compared to other regions. This research aims to know the effect of cervical cancer early detection video on increasing women’s knowledge in the Pasar Baru Village District Karawaci Tangerang City. Quasi-experimental research pre-post-test with control group design. The data were analyzed using paired t-test and an independent t-test. The knowledge average scores comparison between pre-post-test scores for the treatment group (56,39 ± 7.12, p = 0,0001) was higher than the control group (36,81 ± 7.18, p=0,0001). Post-test measurement showed a meaningful difference in average knowledge score between the treatment group and the control group (p=0,0001), with a mean difference of 18.485. Video interventions are more effective at improving women's early detection of cervical cancer than lecture methods.